The Transformation of Post-Communism: Between Liberal Pluralism and Democractic Community - Valantiejus, Vaidotas (Sociologija. Mintis ir veiksmas, 2013)
The main task of this article is to analyze complex relations between post-communism and democracy. More specifically, it aims to understand the interaction of two different forms of society: holistic and pluralistic. The article argues that post-communism is the hybrid condition that includes the alter ego of communism, liberalism and postmodernism. The reflection of triple relations is necessary for the autonomy of post-communism. The relationship between post-communism and communism is analyzed as the problem of post-totalitarianism, between post-communism and liberalism as the problem of democratic liberalization, and between post-communism and postmodernism as the problem of pluralisation of pluralism.